Association of Total Shareholder Return with other value based measures of financial performance - Pandya, Bhargav (Journal of Entrepreneurship, Business and Economics; Vol 2 No 2 (2014), 2014)
Purpose- The purpose of this paper is to examine the relationship between total shareholder return (TSR) and other value based measures like created shareholder value (CSV), market value added (MVA), and economic profit (EP) in Indian banking sector and provide empirical evidences. Design/methodology/approach- The paper uses a sample of 21 listed Indian banks segregated into 10 public sector banks and 11 private sector banks. The study period ranges from year 200-01 to 2009-10. Pooled ordinary least square regression is used to test the relationship between the variables in question. Findings- The results reveal that CSV, EP individually explain the variation in TSR of Indian banks. Whereas, MVA as an individual independent variable does not explain variation in TSR of Indian banks. However CSV, MVA and EP jointly explain variation in TSR of Indian banks. Research limitations/implications- The study was specifically restricted to listed banks in India. It did not consider unlisted banks. Originality/value- Author concludes that individual value based measure should not be blindly used while measuring the shareholder value creation by a firm. Rather, a mix of these measures should be used to accurately measure the shareholder value creation. Research paper Reference to this paper should be made as follows: Pandya, B. (2014). “Association of Total Share-holder Return with other value based measures of financial performance: Evidence from Indian Banking Sector”, Journal of Entrepreneurship, Business and Economics, Vol. 2, No. 2, pp. 26–44.